2020
DOI: 10.3390/nu12082246
|View full text |Cite
|
Sign up to set email alerts
|

Impact of Varying Dosages of Fish Oil on Recovery and Soreness Following Eccentric Exercise

Abstract: Fish oils (FOs) are rich in omega-3 long-chain polyunsaturated fatty acids, which have been purported to enhance recovery of muscular performance and reduce soreness post-exercise. However, the most effective FO dose for optimizing recovery remains unclear. The purpose of this investigation was to examine the effect of FO supplementation dosing on the recovery of measures of muscular performance, perceived soreness, and markers of muscle damage following a rigorous bout of eccentric exercise. Thirty-two colleg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
29
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 14 publications
(39 citation statements)
references
References 54 publications
7
29
3
Order By: Relevance
“…This study follows VanDusseldorp et al, 2020 [ 8 ] who observed reductions in muscle damage and recovery after an acute bout of eccentric resistance exercise with 7.5 weeks of 6 g of n-3 supplementation consisting of a 2:1 ratio of EPA to DHA in resistance-trained males. Therefore, the purpose of this study was to investigate the effect of 33 days of 6 and 8 g of n-3 supplementation on markers of EIMD and muscle recovery after an acute bout of muscle-damaging eccentric resistance exercise in resistance-trained males.…”
Section: Introductionmentioning
confidence: 74%
See 4 more Smart Citations
“…This study follows VanDusseldorp et al, 2020 [ 8 ] who observed reductions in muscle damage and recovery after an acute bout of eccentric resistance exercise with 7.5 weeks of 6 g of n-3 supplementation consisting of a 2:1 ratio of EPA to DHA in resistance-trained males. Therefore, the purpose of this study was to investigate the effect of 33 days of 6 and 8 g of n-3 supplementation on markers of EIMD and muscle recovery after an acute bout of muscle-damaging eccentric resistance exercise in resistance-trained males.…”
Section: Introductionmentioning
confidence: 74%
“…1 ). Conjugated linoleic acid was chosen as the placebo, as it has been used as such in VanDusseldorp et al, 2020 [ 8 ] and is characteristically similar to the omega-3 capsules. Participants were given written and verbal instructions on supplement duration, number of capsules to be taken per day, and dietary restrictions throughout the course of the study.…”
Section: Methodsmentioning
confidence: 99%
See 3 more Smart Citations